2020
DOI: 10.3389/fncel.2020.535549
|View full text |Cite
|
Sign up to set email alerts
|

Prior Hypoxia Exposure Enhances Murine Microglial Inflammatory Gene Expression in vitro Without Concomitant H3K4me3 Enrichment

Abstract: Hypoxia (Hx) is a component of multiple disorders, including stroke and sleep-disordered breathing, which often precede or are comorbid with neurodegenerative diseases. However, little is known about how hypoxia affects the ability of microglia, resident CNS macrophages, to respond to subsequent inflammatory challenges that are often present during neurodegenerative processes. We, therefore, tested the hypothesis that hypoxia would enhance or “prime” microglial pro-inflammatory gene expression in response to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…One speculation is that transcriptional downregulation may occur through epigenetic modifications. Hypoxia targets Jumonji AT-rich interactive domain 1A (JARID1A) activity, which in turn increases Histone H3 lysine 4 (H3K4) trimethylation (H3K4me3), leading to the altered programs of gene expression including CD55 (Zhou et al, 2010;Kiernan et al, 2020). The current study found that dapagliflozin reduced HIF-1α accumulation, upregulated Crry and ameliorated complement over-activation; with the accumulation of HIF-1α stabilized by DMOG, the expression of Crry was decreased.…”
Section: Discussionmentioning
confidence: 57%
“…One speculation is that transcriptional downregulation may occur through epigenetic modifications. Hypoxia targets Jumonji AT-rich interactive domain 1A (JARID1A) activity, which in turn increases Histone H3 lysine 4 (H3K4) trimethylation (H3K4me3), leading to the altered programs of gene expression including CD55 (Zhou et al, 2010;Kiernan et al, 2020). The current study found that dapagliflozin reduced HIF-1α accumulation, upregulated Crry and ameliorated complement over-activation; with the accumulation of HIF-1α stabilized by DMOG, the expression of Crry was decreased.…”
Section: Discussionmentioning
confidence: 57%
“…Zhang et al also revealed that acute hypoxia induces an imbalanced M1/M2 activation of microglia through the NF-κB signaling pathway ( 21 ). Furthermore, even preexposure to hypoxia for 3-6 days can lead to persistent and aberrant inflammatory responses ( 22 ). The present study revealed that compared with 3% O 2 , 1% O 2 increased the expression of proinflammatory cytokines, including IL-6, TNF-α and IL-β.…”
Section: Discussionmentioning
confidence: 99%